ANALISIS OLAHRAGA TENIS MEJA DENGAN KONSEP FISIKA: GERAK PARABOLA - Hidayah, Vivi Nur; Ocktaviani, Tasya Fitri; Saharani, Elsa; Setiaji, Bayu (Jurnal Pendidikan Fisika FKIP UM Metro, 2024)
Table tennis or pingpong is a sport that uses the bet as a striker that is popular among all. The research is aimed at finding out the great influence of the angle of the table tennis service so that the service is performed effectively. The method used is to capture a video when the player performs the service by variing the angles 20°, 40°, 60°, and 90°. Then analyzed using the Tracker application and analysis based on the parabolic equation of motion. The result is that there is a large influence of the angle on the service performed, the larger the angle of elevation then the maximum height will be larger except the angle 60°. The elevation angle affects the maximum distance of the ball.